(untitled) (Global Journal of Management and Business Research, 2013)
The study aimed to examine the correlations among human resources roles, professional competencies and emotional intelligence in the sector of Hotel Industry (5 stars) in the Hashemite Kingdom of Jordan. Data were collected through a questionnaire from a sample of managers (major departments) in the international hotels in Capital Amman. The questionnaire which was developed and distributed during the summer of 2012 includes 14 main dimensions covering the model of study. LISREL Analysis (Linear Structure Model Analysis) is used in the study to verification the correlations among the independent and independent variables. The degree of the positive fitness of the Hypothetical model and test of the results of each hypotheses indicates that achieve an acceptable level (GFI= 0.78 and CFI= 0.87).